Machine Learning Advancements in Urban Traffic Simulation: A Comprehensive Survey - Harshit Maheshwari; Li Yang; Richard W. Pazzi (IEEE Open Journal of Intelligent Transportation Systems)
Urban traffic simulation is useful in many ways to understand, manage, and predict the growing complexities of traffic dynamics within a city. Traditional simulation models often struggle to capture the intricacies of urban traffic patterns, leading to unrealistic simulations, which negatively affect traffic management and urban planning. In recent years, Machine Learning solutions have emerged to enhance various aspects of urban traffic simulation, which is possible by utilizing vast amounts of data and extracting valuable insights. This survey systematically reviews the state-of-the-art Machine Learning techniques applied to urban traffic simulation. By focusing on the practical application of Machine Learning techniques in various studies, we aim to analyze the current research direction, highlight the effectiveness of existing approaches, identify their limitations, and propose potential strategies to improve the performance and applicability of these techniques in real-world scenarios. Another key contribution of this survey is a proof-of-concept case study, which utilizes a basic Reinforcement Learning algorithm to control traffic lights across multiple intersections. The results from this case study demonstrate a significant improvement in vehicle wait time compared to the static baseline method. The code developed for this case study is publicly available, providing a valuable resource for researchers interested in replicating this work or building upon it. This survey aims to bridge the gap between simulation and reality by providing a comprehensive foundational understanding of the subject, critically evaluating the existing limitations in current methodologies, and suggesting future directions to improve performance, adaptability, and usability.